The biological role of the medial olivocochlear efferents in hearing: separating evolved function from exaptation - Smith, David W.; Keil, Andreas (Frontiers in Systems Neuroscience, 2015)
Cochlear outer hair cells (OHCs) are remarkable, mechanically-active receptors that determine the exquisite sensitivity and frequency selectivity characteristic of the mammalian auditory system. While there are three to four times as many OHCs compared with inner hair cells, OHCs lack a significant afferent innervation and, instead, receive a rich efferent innervation from medial olivocochlear (MOC) efferent neurons. Activation of the MOC has been shown to exert a considerable suppressive effect over OHC activity. The precise function of these efferent tracts in auditory behavior, however, is the matter of considerable debate. The most frequent functions assigned to the MOC tracts are to protect the cochlea from traumatic damage associated with intense sound and to aid the detection of signals in noise. While considerable evidence shows that interruption of MOC activity exacerbates damage due to high-level sound exposure, the well characterized MOC physiology and evolutionary studies do not support such a role. Instead, a MOC protective effect is well explained as being a byproduct of the suppressive nature of MOC action on OHC mechanical behavior. A role in the enhancement of signals in noise backgrounds, on the other hand, is well supported by (1) an extensive physiological literature (2) examination of naturally 0ccuring environmental acoustic conditions (3) recent data from multiple laboratories showing that the MOC plays a significant role in auditory selective attention by suppressing the response to unattended or ignored stimuli. This presentation will argue that, based on the extant literature combining the suppression of background noise through MOC-mediated rapid adaptation with the suppression of non-attended signals, in concert with the corticofugal pathways descending from the auditory cortex, the MOC system has one evolved function – to increase the signal-to-noise ratio, aiding in the detection of target signals. By contrast, the MOC system r